How to build a model to improve response - Clarke, Stuart (Henry Stewart Talks, 2008)
What is response analysis?, The steps in building a targeting model (CRISP), How analytical techniques such as RFM, classification trees and regression analysis can be applied in order to identify the best targets for a direct marketing campaign, Choice of software and modelling technique, Model testing and evaluation, Case study example